2018
DOI: 10.3389/fphys.2018.01426
|View full text |Cite
|
Sign up to set email alerts
|

Twist1-Haploinsufficiency Selectively Enhances the Osteoskeletal Capacity of Mesoderm-Derived Parietal Bone Through Downregulation of Fgf23

Abstract: Craniofacial development is a program exquisitely orchestrated by tissue contributions and regulation of genes expression. The basic helix–loop–helix (bHLH) transcription factor Twist1 expressed in the skeletal mesenchyme is a key regulator of craniofacial development playing an important role during osteoskeletogenesis. This study investigates the postnatal impact of Twist1 haploinsufficiency on the osteoskeletal ability and regeneration on two calvarial bones arising from tissues of different embryonic origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
3
11
0
Order By: Relevance
“…The higher rich factor indicated higher enrichment regeneration compared to mesoderm derived parietal bone. 4,8,10,11 In our study, we further revealed another feature in the frontal and parietal bone with a distinct miRNA pattern.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The higher rich factor indicated higher enrichment regeneration compared to mesoderm derived parietal bone. 4,8,10,11 In our study, we further revealed another feature in the frontal and parietal bone with a distinct miRNA pattern.…”
Section: Discussionsupporting
confidence: 67%
“…Since the establishment of dual tissue origins in the frontal bones and parietal bones, neural crest‐derived frontal bone have been found with superior osteogenic capacities for bone regeneration compared to mesoderm derived parietal bone . In our study, we further revealed another feature in the frontal and parietal bone with a distinct miRNA pattern.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Ideally, a suitable cytokine or drug would be sufficient to initiate the endogenous program for bone healing. FGF and Wnt signaling are able to quicken bone healing from injury (Xu et al, 2007;Quarto et al, 2009Quarto et al, , 2010Quarto et al, , 2018Behr et al, 2010;Ichikawa et al, 2015;Li et al, 2015;Hu et al, 2017;Wu et al, 2017;Doro et al, 2019). BMPs, receptors, and intracellular Smads have robust expressions in the periosteum after a fracture, and their expressions are detectable in endothelial cells that associated with new bone formation (Yu et al, 2010).…”
Section: Bmp Signaling In Calvarial Regeneration Bmps and Calvarial Rmentioning
confidence: 99%
“…The calvaria provides important protection for the growth and formation of the brain, and its growth is concordantly orchestrated across developmental stages. Since the establishment of the dual-tissue lineages of the calvaria (Jiang et al, 2002), studies are focusing on region-dependent differential regulation of calvarial bone development (Quarto et al, 2009(Quarto et al, , 2010(Quarto et al, , 2018Wiren et al, 2011;Ichikawa et al, 2015;Li et al, 2015;Doro et al, 2019). On one hand, the region-dependent roles of evolutionally conserved signaling pathways in calvarial bones are under clarifying (Quarto et al, 2009;Behr et al, 2010;Li et al, 2010;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%